Investigation into Effects of Scanning Speed on in Vitro Biocompatibility of Selective Laser Melted 316L Stainless Steel Parts - Shang Yitong; Yuan Yanping; Zhang Yongzhi; Li Dongfang; Li Yansheng (MATEC Web of Conferences, 2017)
In recent years, selective laser melting (SLM) has gained an important place in fabrication due to their strong individualization which cannot be manufactured using conventional processes such as casting or forging. By proper control of the SLM processing parameters, characteristics of the alloy can be optimized. In the present work, 316L stainless steel (SS), as a widely used biomedical material, is investigated in terms of the effects of scanning speed on in vitro biocompatibility during SLM process. Cytotoxicity assay is adopted to assess the in vitro biocompatibility. The results show the scanning speed strongly affects the in vitro biocompatibility of 316L SS parts and with prolongs of incubation time, the cytotoxicity increase and the in vitro biocompatibility gets worse. The optimal parameters are determined as follows: scanning speed of 900 mm/s, laser power of 195 W, hatch spacing of 0.09 mm and layer thickness of 0.02 mm. The processing parameters lead to the change of surface morphology and microstructures of samples, which can affect the amount of toxic ions release, such as Cr, Mo and Co, that can increase risks to patient health and reduce the biocompatibility.